Thelephora dominicana (Basidiomycota, Thelephorales), a new species from the Dominican Republic, and preliminary notes on thelephoroid genera - Vizzini, Alfredo; Angelini, Claudio; Losi, Cristiano; Ercole, Enrico (Phytotaxa, 2016)
A new species of Thelephora, characterized by more or less infundibuliform basidiomes and globose to subglobose strongly echinulate basidiospores, is described from the Dominican Republic based on morphological and molecular data (analyses of LSU and ITS sequences). Phylogenetic insights on genera in the Thelephorales are also provided.